2006
DOI: 10.1016/j.ymthe.2005.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Lentiviral Vector Stimulates both CD4 and CD8 T Cell Responses to an Ovalbumin Transgene

Abstract: Lentiviral vectors encoding antigens are promising vaccine candidates because they transduce dendritic cells (DC) in vivo and prime CTL responses. Here we examine their stimulation of antigen-specific CD4(+) T cells, critical for protective immunity against tumors or infectious disease. We constructed lentiviral vectors (lentivectors) expressing ovalbumin, which was secreted (OVA), cytoplasmic (OVAcyt), or fused to either invariant chain (Ii-OVA) or transferrin receptor (TfR-OVA) sequences, targeting the MHC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 43 publications
5
125
0
Order By: Relevance
“…Consistent with in vitro results, recent studies show that direct administration of lentivector via intravenous or subcutaneous injection results in transduction of Ag presenting cells (APCs) including DCs in the spleen [57][58][59] , and in the draining lymph nodes 18,46,60 . Besides transduction of DCs in vivo, recombinant lentivector also results in transduction of B cells in the spleen after intravenous injection 57,59 or in the draining LNs after subcutaneous immunization.…”
Section: Transduction Of Apcs With Recombinant Lentivectorsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with in vitro results, recent studies show that direct administration of lentivector via intravenous or subcutaneous injection results in transduction of Ag presenting cells (APCs) including DCs in the spleen [57][58][59] , and in the draining lymph nodes 18,46,60 . Besides transduction of DCs in vivo, recombinant lentivector also results in transduction of B cells in the spleen after intravenous injection 57,59 or in the draining LNs after subcutaneous immunization.…”
Section: Transduction Of Apcs With Recombinant Lentivectorsupporting
confidence: 63%
“…Besides transduction of DCs in vivo, recombinant lentivector also results in transduction of B cells in the spleen after intravenous injection 57,59 or in the draining LNs after subcutaneous immunization. But, B cells isolated from mice immunized with recombinant lentivector did not induce naïve TCR transgenic T cells proliferation.…”
Section: Transduction Of Apcs With Recombinant Lentivectormentioning
confidence: 99%
“…109 Therefore it is crucial not only to evaluate the TAAspecific immune response but also the influence of the treatment on tumor growth. Whereas Rowe et al 110 showed significantly improved protection of direct administration of an OVA-encoding lentiviral vector against a subsequent tumor challenge, no data was shown about the therapeutic efficacy of this treatment. Using a similar OVA-encoding lentiviral vector we could show that direct administration of lentiviral vectors offers increased protection to a subsequent tumor challenge compared to DC vaccination and a significantly improved survival of tumor bearing mice.…”
Section: Direct Administration Of Lentiviral Vectorsmentioning
confidence: 99%
“…[128][129][130] For direct administration of lentiviral vectors, several groups have shown that both a CTL response and an antigen-specific CD4 + T-cell response can be induced. 98,104,110 However, not much data is available on the role of CD4 + T-cell help in CTL induction. Esslinger et al showed that CD4 depletion reduces primary CTL response on direct administration of lentivirus.…”
Section: Immunogenicity Of Lentiviral Vectorsmentioning
confidence: 99%
“…Therefore, lentivectors have thus been proposed to be an ideal vector tool for vaccine delivery. 20,[24][25][26][27][28][29][30][31][32][33] Based on the study of Sindbis virus, a member of the Alphavirus genus and the Togaviride family, we have reported a mutant Sindbis virus glycoprotein, (SVGmu) which can specifically bind to DC-specific intracellular adhesion molecule (ICAM) 3 grabbing non-integrin (DC-SIGN, CD209). 34 DC-SIGN is a C-type lectin-like receptor and is expressed on DCs and macrophages.…”
Section: Introductionmentioning
confidence: 99%